2018
DOI: 10.1080/10408398.2018.1479830
|View full text |Cite
|
Sign up to set email alerts
|

Betalains, the nature-inspired pigments, in health and diseases

Abstract: Betalains are unique nitrogen-containing pigments found exclusively in families of the Caryophyllales order and some higher order fungi, where they replace anthocyanin pigments. Betalains, consisting of betacyanins and betaxanthins are generally used as color additives in food. This review discusses on the favorable effects of acute and chronic consumption of betalains, whose edible sources consist primarily of red beetroots (Beta vulgaris) and prickly pears (fruit of the Opuntia genus of cacti). Moreover, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
100
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(106 citation statements)
references
References 118 publications
1
100
0
5
Order By: Relevance
“…The authors also correlated the protective effects of betanin in the face of inflammation to its antioxidative properties. Histopathological examination has also revealed that betanin ameliorated lung damage with significantly lower level of edema, hemorrhage, neutrophil infiltration and alveolar septa thickening [70]. Comparable findings as well have been demonstrated in a model of acute myocardial infarction induced by three daily 100 mg/Kg isoproterenol doses.…”
Section: Betanin and Inflammationsupporting
confidence: 55%
“…The authors also correlated the protective effects of betanin in the face of inflammation to its antioxidative properties. Histopathological examination has also revealed that betanin ameliorated lung damage with significantly lower level of edema, hemorrhage, neutrophil infiltration and alveolar septa thickening [70]. Comparable findings as well have been demonstrated in a model of acute myocardial infarction induced by three daily 100 mg/Kg isoproterenol doses.…”
Section: Betanin and Inflammationsupporting
confidence: 55%
“…The health-promoting activities of betalains have been extensively studied in the context of their anticancer, anti-in ammatory, hepatoprotective and have been commercialized as dietary supplements and used in food colorants in the food industry (Kaur et al 2018). The antioxidative capacity of betalain has been studied extensively in the context of scavenging the free-radicals, and the blood pressure-lowering capacity of betalain on the nervous system (Rahimi et al 2019) has tempted us to look into these characteristics in reducing the complications of glaucoma that are induced due to increased pressure on the retinal nerves in causing apoptosis of the ganglion cells.…”
Section: Keypointsmentioning
confidence: 99%
“…The radical scavenging activity of betalains has been recently reviewed by Rahimi et al [62] and Ninfali et al [63].…”
Section: Anti-oxidant and Anti-inflammatory Activitymentioning
confidence: 99%
“…We have found that low doses of betanins (<100 g/ml) are not cytotoxic to SV40 t-antigen-and papilloma virus-immortalized human lung epithelial cells. On the other hand, betanins are cytotoxic at low concentrations and in a dose-response fashion to some cultured tumor cells, but not all [62]. Nowacki et al [67] suggested that betanininduced apoptosis was dependent on p53 status, i.e., normal p53 imparts resistance to betanin cytotoxicity.…”
Section: Betanins Cytotoxicity Of Cultured Cellsmentioning
confidence: 99%